Factors governing phytoplankton community in the Can Gio mangrove biosphere reserve, Vietnam - Pham, Thanh-Luu (Vietnam Journal of Marine Science and Technology, 2019)
This paper covers spatial and temporal variations in phytoplankton communities and physico-chemical water properties in the Can Gio Mangrove Biosphere Reserve (CGMBR), Vietnam based on field measurement conducted in dry and wet seasons of 2010. Phytoplankton samples and water parameter data were collected from nine stations in the CGMBR. A total of 86 species were recorded with clear dominance of Bacillariophyceae, which formed above 90% of the total phytoplankton abundance with average of 48,000 cell/l in dry season and 35,000 cell/l in wet season. Although Chaetoceros and Coscinodiscus were the two most diverse genera, Skeletonema showed high abundance during the studied period. Among the ten environmental parameters tested in this study, salinity, turbidity, nitrate, ammonium and silicon dioxide were found to be significantly different between seasons. On the other hand, no significant difference was found between stations for the studied physico-chemical parameters. Results of CCA indicated that the phytoplankton assemblage in CGMBR was influenced by salinity, turbidity, nitrate, ammonium and phosphate concentration. This is the first study simultaneously investigating the phytoplankton communities and their environment in this area and it is essential to set up the baseline of future studies